Water pollution evaluation as consequent of old wells oil exploration - Sriyani Sopeana; Eddy Ibrahim; Muhammad Faizal (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
This research was aimed to investigate effect of oil spills on surface water from exploration in Dutch well.The investigation was carried out by in situ measurement of some parameters.Water sample was collected by grab sampling method and the analysis was conducted at Laboratory of Environment Badan Lingkungan Hidup dan Penelitian Pengembangan (BLHPP) Kabupaten Musi Banyuasin.The measurement result showed that some parameters did not fulfill the requirement of Standar Quality for Domestic Water Regulation according to Government Regulation No. 82 year 2001 i.e. COD and Oil&Fat content. The surface water and shallow ground water quality had some parameters that did not comply with standar quality according to regulation such as BOD, COD, DO, and oil-fat content.Calculation of pollution indeks (PI) showed that domestic water has 3.26 and was categorized into slightly polluted. At surface water in Angit River, the calculation of PI showed that upstream river was slightly polluted (3.23), while midstream was slightly polluted (3.22) and in downstream river was mildly polluted (9.60).